Demographic and aetiological factors of paediatric status epilepticus at Red Cross War Memorial Children's Hospital: 2016-2018 - Nsanta, Sarahlouise (Department of Paediatrics and Child Health, 2024)
Background: Status epilepticus is a common medical neurological emergency in childhood which is often serious and life threatening. There is paucity of data with regard to aetiology and demographics of affected children in resource-limited countries. Objective: To describe the demographics and the common causes of convulsive status epilepticus in our paediatric population. Methods: A retrospective review of the clinical records of children who presented in convulsive status epilepticus to the medical emergency department (ED) of Red Cross War Memorial Children's Hospital (RCWMCH), in Cape Town, South Africa, between May 2016 and May 2018 was completed. Demographics, clinical characteristics and characterisation of convulsive status epilepticus were assessed. Results: Of 119 children, 63 (53%) were male; their median age was 29.6 (IQR 14.8-76.1) months: 22 (18%) were under one year of age, 63 (53%) were 1-5 years, and 34 (29%) >5 years. There were 31 (26%) children who were moderately-severely underweight-for-age; 5 (4%) children were HIV-infected. Fifty (42%) children were known to have epilepsy of whom ten reported poor compliance with their antiseizure medication, 20 (17%) children had cerebral palsy, 40 (34%) had developmental delay, and nine (8%) had a history of previously treated tuberculosis (TB)- of whom six had pulmonary TB, one TBM, one with extrapulmonary TB and one with disseminated TB. During the captured episode of CSE, 55 (51%) children were brought by ambulance, the rest self-presented using private or hired transport; 33 children received a benzodiazepine agent pre-hospital, 19 had aborted by the time of arrival at hospital, but 72 (62%) required antiseizure medication in the ED. In their seizure semiology, 82 (71%) children had generalised convulsive seizures and 34 (29%) had focal seizures; with 85 (73%) being prolonged events and 32 (27%) being multiple events. Aetiology according to ILAE classified 74 (62%) as secondary to acute infective cause, 12 (10%) had an electroclinical syndrome, 9 (8%) were remote and 25 (22%) were unknown. A recorded tympanic membrane temperature of ≥38°C was found in 41 (37%) of 112 children, supporting febrile status epilepticus in these children. Imaging was undertaken in 45/119 (38%), with 28 (62%) being abnormal. Cerebral spinal fluid findings were abnormal in 7 (12%) of 57 children who had lumbar puncture done and there were no deaths in the cohort. Most children, 87 (73%), were stabilised adequately for admission in the short stay ward, however eight required admission to ICU. Conclusion: Acute infections are the most common cause of CSE in our setting with the highest proportion of children presenting in the infantile age range, this is concordant with other studies, but our results show a higher percentage of infective causes.